Placental polyp after normal vaginal delivery: a rare diagnostic dilemma - Agarwal, Himanshi D.; Desai, Archish I.; Gheewala, Amisha S.; Parikh, Sonam K.; Shukla, Ashwini A.; Dudhwala, Princy R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Placental polyp is retained placental tissue within the endometrial cavity, which forms a nidus for inflammation and bleeding. Placental polyp is a rare entity with an incidence of less than 0.25% of all pregnancies as reported. Here, we report a case of 23-year-old P2L2 woman with complaints of intermittent vaginal bleeding since her recent normal vaginal delivery, 1.5 months back. A polypoid mass (51×41 mm) with abundant vascularity was detected as retained products of placenta (RPOC) within the endometrial cavity by imaging studies. A combination of polypoidal mass within the endometrial cavity with normal beta human chorionic gonadotropin (hCG) of <2.0 mIU/ml raising the suspicion of retained products of placenta or trophoblastic neoplasms. After yielding an unsatisfactory biopsy containing only fibrin deposition, total hysterectomy was performed due to profuse bleeding during biopsy. The uterus specimen showed slight globular enlargement with presence of a red-coloured polypoid mass within the endometrial cavity with rough outer surface and fragile consistency. The histological specimen of the protruding lesion, from the exaggerated placental implantation site, showed intermediate trophoblastic cells infiltrated into the myometrium, which might lead to the diagnosis of placental polyp. However, since placental polyp and uterine arteriovenous malformation have similar clinical characteristics, it is important to accurately identify and differentiate between them to ensure optimal treatment therapy. Definite diagnosis is ultimately made by histopathological examination. We report here a case that is suggestive of either a placental polyp or uterine arteriovenous malformation and will discuss the differential diagnoses and treatments for both diseases, based on a literature review.